Pengembangan Media Pembelajaran Berbasis Google sites Pada Materi Cahaya Kelas VIII SMP - Iwi Tarno; Nurwanti Fatnah; Leo Muhammad Taufik (UNIB Press, 2023)
Google sites-based learning that has been tested on junior high school students on light material is the method taken by teachers in online learning by utilizing technological media. Google sites learning has never been carried out at SMP Muhammadiyah 2 Cirebon, so researchers have an interest in improving the quality of education in an online environment. which requires learning to continue. The research method used was the 4D model of Research and Development method. Analysis and techniques for collecting data from library studies and field studies which include observation, interviews and distributing student response questionnaires. As for determining the class VII B sample, then to analyze using a scale conversion of four. Based on the results of the analysis and conclusions in the discussion chapter, the authors make the following suggestions: science subject teachers need to make varied learning and increase knowledge in technological media to improve efficient and advanced learning.